The Effect of Kafa’ah on Marriage from the Perspective of Mashlahah: An Analysis of the Maliki Madhhab - Surya, Asmedi; Jaafar, Azhar; Ichsan, Muhammad; Aryanti, Yosi (Jurnal Elsyakhshi, 2024)
Hirfah (occupation) is one of the criteria for kafa’ah (compatibility) in marriage according to most schools of Islamic thought. However, the Maliki school of thought does not consider Hirfah essential for kafa’ah. According to Maliki scholars, occupation does not impact the benefit or validity of a marriage. This study aims to analyze the Maliki perspective on Hirfah as a criterion for kafa’ah and its implications for marital benefit. This research uses a qualitative approach with content analysis, this research explores the Maliki school’s stance on kafa’ah criteria in depth. The findings indicate that the Maliki school does not include Hirfah as a criterion for kafa’ah, emphasizing instead that religious compatibility is the principal factor. This position is influenced by the cultural context of Imam Malik’s time, when women’s employment was uncommon. However, in contemporary contexts, many women work prior to marriage, which affects their socioeconomic status and, consequently, community perspectives. This shift has led Hirfah to be increasingly viewed as a relevant factor in assessing kafa’ah and the benefit of marriage today.